Bioprosthetic or native aortic scallop intentional laceration to prevent iatrogenic coronary artery obstruction technique in transcatheter aortic valve-in-valve procedures: a single-center initial experience. Issue 3 (4th March 2021) - Tagliari, Ana Paula; Miura, Mizuki; Gavazzoni, Mara; Haager, Philipp K.; Russo, Giulio; Pozzoli, Alberto; Zuber, Michel; Jörg, Lucas; Rickli, Hans; Gennari, Marco; Maisano, Francesco; Taramasso, Maurizio
Abstract : Supplemental Digital Content is available in the text Abstract : Aim: To describe six cases using the bioprosthetic or native aortic scallop intentional laceration to prevent iatrogenic coronary artery obstruction technique to prevent coronary artery obstruction during transcatheter aortic valve-in-valve procedures. Methods: All patients presented degeneration of a bovine pericardium bioprosthesis [four Trifecta (19, 21, 23, and 25 mm); two Mitroflow (25 and 27 mm)] resulting in severe aortic stenosis ( n  = 5) or severe aortic regurgitation ( n  = 1). Procedures were performed under fluoroscopic and echocardiography guidance, and the transfemoral access was used to deliver a self-expanding valve. Data are expressed as frequency or median (Q1 –Q3 ). Results: Age, EuroScore II, and Society of Thoracic Surgeons score were 81 years (75–83.2), 2.9% (2.6–10.7), and 2.7% (2.3–3.2), respectively. Median left and right coronary heights were 9.1 mm (6.2–10.3) and 12.4 mm (10–13.5), respectively, with a median virtual transcatheter heart valve-to-coronary distance of 2.9 mm on the left and 4.6 mm on the right side. Isolated left leaflet laceration was planned in four patients, and bileaflet in two. One unsuccessful right leaflet laceration was reported, corresponding to the first patient (success rate 87.5%). All other seven leaflets lacerations were successfully performed, with no intraprocedure complications. No coronary obstruction, in-hospital death, valve complication, cardiovascular event, or pacemaker implantation were reported. All patients are being followed in routine outpatient visits, and no adverse events were registered. Conclusion: The high procedural success and low complication rate reported in this initial experience, demonstrates that the bioprosthetic or native aortic scallop intentional laceration to prevent iatrogenic coronary artery obstruction technique can be a viable solution to prevent coronary obstruction in selected patients undergoing valve-in-valve procedures. Operator experience, periprocedural imaging and teamwork are essential to enable an accurate and successful procedure.